Corporate social responsibility and supply chain: A study for evaluating corporate hypocrisy with special focus on stakeholders. (10th February 2021) - Tiwari, Mohit; Tiwari, Tripti; Sam Santhose, Samuel; Mishra, Lokanath; MR, Rejeesh; Sundararaj, Vinu
Abstract: Supply chains are intended to become the essential part of this global competitive world as organizations are seeking to formulate strategized advantages. To put it differently, most of the companies are aiming to adopt new businesses and raise the competition in the global market. For this, most of the companies or organizations are choosing strategies such as corporate social responsibility and supply chain management that allow the companies to ensure financial strengthening. Moreover, stakeholders and customers have raised their concerns towards corporate social responsibility with respect to global supply chain and ensured to act in a socially responsible way. It is believed that majority of the organizations are placing high importance on implementing corporate social responsibility or CSR activities in order to enhance the whole business. The active participation of companies in CSR activities will always benefit them in terms of profit, virtues and other moral standards. Usually, corporate firms exhibit their virtues ignoring the moral standard, which eventually reveals the nature of hypocrisy. Corporate hypocrisy is a context when companies or organizations assure the public to do something in corporate social responsibility context and end up doing entirely different. Keeping this in mind, the current study aims to reveal the hidden nature of corporate hypocrisy and its effect on inner stakeholders explicitly focusing on the employees' observations on corporate hypocrisy; examine the hypocritical behaviour of the reputed firms towards the consumers, which in turn affects the supply chain globally. For this, data analysis will be carried out with consumer firms across countries. Results show that firms are completely held responsible for their behaviour eventually defaming reputation.